On plate 24 by Maria Sibylla Merian in Metamorphosis insectorum surinamensium, and some types of Prioninae (Coleoptera: Cerambycidae) - Santos-Silva, Antonio; Nearns, Eugenio H. (Zootaxa, 2023)
The status of the two specimens of Prioninae seen on Merian’s plate 24 (1705) is discussed, and considered as being Mallodon spinibarbis (Linnaeus, 1758). Prionus similis Schönherr (1817) is revalidated and placed in incertae sedis in Prioninae. Information on the types of Cerambyx spinibarbis Linnaeus, 1758, C. cinnamomeus Linnaeus, 1758, and C. melanopus Linnaeus, 1767 are provided.